A SURVEY ON THE EFFECTS OF MEDITATION IN STUDENTS OF GRADE III - Kashid, Prajkta; P. S. Bansode (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study attempts a survey on effects of meditation in students of grade III. For this purpose, 35 students were selected specifically of grade 3, from MIT Vishwashanti Gurukul School, Kothrud, Pune. We used 3 domains and 11 statements were formed. The domains were Self - Expression, Self - Regulation and Social behavior. The percentage of each domain were calculated. For the domain self – Expression, 80% students responded as “Yes”, 6% said “No”, and 14% students responded “Can’t say". For the domain Self – Regulation, 81% students responded “Yes”, 7% said “No”, and 12% students responded “Can’t say". For the domain self - Regulation 81% students responded “Yes”, 7% said “No”, and 12% students responded “Can’t say".